PROSEDUR HUKUM PELEPASAN TANAH ULAYAT UNTUK PEMBANGUNAN INFRASTRUKTUR PEMERINTAH - Kornelius Ayub Romario Simanulang (Fakultas Hukum Universitas Udayana, 2023)
This study aims to find out about the legal procedures for releasing customary land under Indonesian laws and regulations for the development of government infrastructure. The method used is normative juridical, with a statutory approach and a case approach, which is analyzed using qualitative descriptive analysis techniques. The result of this study is that the land release procedure is contained in Law No. 30 of 2009 on Electricity, Law No. 2 of 2012 on Land Procurement for Public Interests, and Law No. 39 of 2014 on Plantation. The essence of land release is the provision of compensation to the rightful party or customary law community. Compensation is not only in the form of money but can be done in other ways, according to the law. Verdict No. 18/Pdt.G/2019/PN Jap is an example of a case of land tenure without relinquishment. Customary land is owned and built by the state for public services, and a certificate of land rights is issued. Legitimate land certificates without evidence of land release are meaningless in customary land disputes.